Rosaceae endémicas del Perú - Mendoza, Wilfredo (2006)
The Rosaceae are represented in Peru by 24 genera and 113 species (Brako & Zarucchi, 1993; Mendoza, 2005; Ulloa Ulloa et al., 2004), between herbs, shrubs and trees. Here we recognize 14 endemic species in four genera. These endemic species are found mainly in Pluvial Montane Forests, Humid Montane Forests and Paramo regions, from 1900 to 3800 m elevation. Six endemic species have been recorded within Peru’s protected areas system.